Statistical Studies as a Means of Inductive Thinking in the Field of Education - RIfqi, Muhammad Novel; Diantini, Helen; Setiawan, Kayla Zahra; Aninda, Rita; Mahardika, I Ketut; Mahmoudi, Kendid (International Journal of Education, Information Technology, and Others, 2024)
Statistical studies in education play a role important role in quantitative research. It works as a powerful, enabling inductive thinking tool researchers to uncover deep patterns and relationships education data. This discussion explores the significance ofstatistical representation in research quantitative and its role in improving our understanding of education. This emphasizes how statistical representation is not only simplify complex data but also generate new knowledge in the field education. By examining its use in various aspects of educational research, this discussion highlights the challenges and benefits of statistical representation in education and its important role in provide policy information and decisions decisions in the education sector